Micro-Foundations of Diverging Economic Policies: Keynesian, Behavioural, Neoclassic - Ronald Schettkat (Intereconomics)
Abstract Germany’s austerity-oriented economic policy is the wrong approach. Markets need demand stimulation to achieve full use of resources, argues Krugman, a Keynesian economist. Neoclassical economists have been warning that expansionary macroeconomic policies are not only useless but can even be harmful (e.g. Phelps). These stark differences in the evaluation of economic policy proposals are deeply rooted in their underlying microeconomic reasoning, in the theories of the motivation and behaviour of economic agents as investors, workers, consumers and speculators as well as their interactions. The claim of missing micro-foundations in Keynes’s theory is false. In contrast, recent findings of behavioural economics have strongly confirmed Keynes’s micro-foundations that lead to his macroeconomic conclusions.